Theoretical issues in medical library and information sciences' articles published in scopus and web of science databases: A scoping review - Mohammadhiwa Abdekhoda; Hasan Ashrafi-Rizi; Fatemeh Ranjbaran (Wolters Kluwer Medknow Publications, 2023)
Nowadays, professions with stronger theoretical background usually have a better standing among other academic fields. The field of Medical Library and Information Science (MLIS) also requires developments in theoretical issues to increase its ranking and provide more effective support services and higher quality research. The aim of this study was to conduct a scoping review of publications in MLIS in Scopus and Web of Sciences databases to identify the underlying theoretical issues in this field. The research method was a scoping review conducted in February 2022. Articles published in the field of MLIS for which the main theme or research outcomes were based on theoretical foundations, patterns, frameworks, theories and models, and without limitation on time were retrieved from Web of Science and Scopus databases. The retrieved articles were analyzed after necessary screening and evaluation. Based on the determined criteria, 49 articles were eventually analyzed. Patterns, theories, frameworks, and models used in the articles have been categorized into six general groups: (1) information (general) and information literacy; (2) models of evaluation and support services in libraries and information centers; (3) clinical, embedded librarianship, and professional librarianship; (4) scientometrics, selection and evaluation of articles, journals, and serials; (5) open access content; and (6) psychological and sociological models. The results indicate that published articles in the field of MLIS have used a considerable range of models, theories, and frameworks as the most important elements of theoretical concepts. These models, theories, and frameworks have been categorized into six main groups, a number of which have been involving collection development, organization of material, and most have been overseeing the distribution of information and support services in libraries and information centers. Whereas MLIS is an interdisciplinary field with specific applications for access to and distribution of information, it still has considerable potential for presenting models, frameworks, and theories.